Research on load characteristics of levitation chassis of the normal-conducting maglev vehicle under fault conditions - CAO Hui; WU Xingwen; XIONG Jiayang; ZHENG Yuhao; CHI Maoru (机车电传动)
Aiming at the potential failure conditions of the medium and low speed normal-conducting maglev vehicles during operation, the load characteristics of the levitation chassis were studied. Firstly, a dynamic model was established according to the actual parameters and the vibration characteristics were analyzed, to study the displacement characteristics of the levitation chassis under the fault conditions such as electromagnet failure and air spring failure. Then the load characteristics of the levitation chassis were analyzed under fault conditions; the strength of its parts was assessed. The results show that the maglev vehicle body and levitation chassis are connected indirectly by a sliding platform, leading to diversified vibration forms. Under the electromagnet failure condition, the levitation chassis under relatively large displacement at the centroid collides with the track, resulting in a sudden load change of the levitation chassis. Compared with the normal operating conditions, the stress of the longitudinal beam increases by 3.87 times to the maximum when the left electro-magnet fails, and the stress of the supporting arm increases by 2.59 times and 8.11 times to the maximum respectively when the left rear air spring fails and the emergency landing occurs. The current study on the load characteristics of the levitation chassis under fault conditions can provide a reference for the fatigue life calculation and structural strength design.